Numerical simulation of brine discharges from desalination plants into ambient waters - Pham, Thi Hong Nhung. (2009)
The final year project (FYP) is to study on “Numerical simulation of brine discharges from desalination plants into ambient waters”. The project focuses on two main issues in integral modeling of brine discharge. The first one is to apply the existing Wang & Law (2002) integral model, which is to predict the behavior of positively buoyant jets, for the case of negatively buoyant jets. The second one is to further develop the integral model to achieve better model prediction with reference to related past research works. With the method of integral modeling, the kinematic equations are integrated across the flow, yielding a set of ordinary differential equations under the further assumption of self-similarity for the cross-sectional velocity and tracer concentration distributions. To solve the system of equations, a closure equation based on the entrainment hypothesis is commonly adopted and settling the entrainment coefficient α appropriately then becomes a critical step in the model implementation. In the present study, instead of adopting the conventional empirical expression of α as in Wang & Law (2002) model, we resolve the entrainment non-uniformity by incorporating the conservation equation of kinetic energy in addition to the mass, momentum and buoyancy conservation equations, which led to a universal formulation of α as a function of the local flow properties irrespective of the direction of the initial buoyancy, local angle of the trajectory, local concentration-to-velocity spread ratio and an integral concerning the local profiles of the Reynolds shear stress. The model predictions are shown to compare fairly well with existing experimental results for negatively buoyant jets especially at the initial stage of buoyant jets. The various comparisons in the gross flow characteristics, such as the trajectory and centerline minimum dilution profiles will be elaborated later in this report.